DISTINCTIVE APPROPRIATIONS OF THE BEACH: A HISTORICAL-SOCIOLOGICAL APPROACH IN THE CONTEXT OF BRAZILIAN COASTAL LEISURE (Revista de História Regional, 2024)
This text aims to present the historical-social process of the development of maritime leisure and, in parallel, to discuss the systems of distinction and the symbolic conflicts established within the scope of Brazilian coastal leisure. In methodological terms, it is a historical-sociological research with an exploratory dimension of literature and documents socialized on the web. Regarding the analysis of the empirical material collected, the theoretical references of Pierre Bourdieu and Norbert Elias. After collecting and analyzing the data, it was found that the beach was not always reserved for leisure activities. On the contrary, on a long-term scale, social agents appropriated the coast for recreational purposes. However, regardless of the types of appropriation of the space, the beach has routinely been marked by inequalities and symbolic strife between people. Such conflicts, in turn, remain current and dissolve the thesis of the beach as a democratic space.
Keywords: Leisure; Beach; Pierre Bourdieu; Beach holiday; Sociology of Leisure